PENDAMPINGAN PUBLIC SPEAKING PADA RISMA (REMAJA ISLAM MASJID) SMPN 45 BANDUNG) - Wisudawaty, Hanna; Dianita, Indria Angga (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Public speaking is an important skill that can affect one's performance in public. The ability to speak confidently, clearly and convincingly is key to success when speaking in public, including to academic, professional and social audiences. This activity highlights the importance of mastering Public Speaking in improving speaking performance and delivering material in public.This activity was carried out at SMPN 45 Bandung with participants from the extracurricular activities of the Islamic Youth Mosque. This training aims to improve the Public Speaking performance of extracurricular members of the Islamic Youth Mosque who are still not maximized in delivering material in public. This activity was attended by 30 participants with resource persons and activity assistants from the Telkom University Lecturer Team with a background in Communication Science expertise. By mastering public speaking, good public speaking skills can boost confidence, influence audiences more effectively, and deliver messages more clearly and convincingly. In addition, public speaking skills help reduce anxiety, boost confidence and eliminate the fear of public speaking, and open up opportunities to achieve success in various career fields. Thus, investing in the development of public speaking skills is an important step towards achieving good performance and an important asset in personal and professional life.